IMPROVING STUDENTS' CREATIVE THINKING ABILITY THROUGH PJBL BASED ON VIDEO ANIMATION OF WESTERN VOYAGES TO THE NUSANTARA IN THE SUBJECT OF INDONESIAN HISTORY DURING THE AGE OF WESTERN INFLUENCE - Meihan, Andre Mustofa; Tersta, Friscilla Wulan; Kurniawanti, Merci Robbi (Paedagoria : Jurnal Kajian, Penelitian dan Pengembangan Kependidikan, 2025)
Abstract:   Creative thinking skills for students are needed in facing changes and challenges in the dynamic era of globalization. This study aims to determine how the effectiveness of using PjBL based on animated videos of western Voyages routes to the nusantara in improving students' creative thinking skills in Indonesian history courses during the era of western influence. The research method used is Pre-Experimental Designs, with the form of designs used, namely One-Group Pretest-Posttest Design. Based on the results of the study, it can be seen that the use of PjBL based on animated videos of western voyages routes to the nusantara is proven to be effective in improving students' creative thinking skills in Indonesian history courses during the era of western influence. This is based on the results of the paired sample t-test obtained Sig. (2-tailed) of 0.000 <0.05. This shows that there is a significant difference between the value of students' creative thinking skills before and after using PjBL based on animated videos of western Voyages routes to the nusantara. Abstrak: Kemampuan berpikir kreatif bagi mahasiswa sangat dibutuhkan dalam menghadapi perubahan dan tantangan di era globalisasi yang dinamis. Penelitian ini bertujuan untuk mengetahui bagaimana efektivitas penggunaan PjBL berbasis video animasi rute pelayaran bangsa barat ke nusantara dalam meningkatkan kemampuan berpikir kreatif mahasiswa pada matakuliah sejarah indonesia zaman pengaruh barat. Metode penelitian yang digunakan adalah Pre-Experimental Designs, dengan bentuk designs yang digunakan yaitu One-Group Pretest-Posttest Design. Berdasarkan hasil penelitian dapat diketahui bahwa penggunaan PjBL berbasis video animasi rute pelayaran bangsa barat ke nusantara terbukti efektif dalam meningkatkan kemampuan berpikir kreatif mahasiswa pada matakuliah sejarah Indonesia zaman pengaruh barat. Hal ini didasarkan atas hasil uji paired sample t-test diperoleh nilai Sig. (2-tailed) sebesar 0,000 < 0,05. Hal ini menunjukan adanya perbedaan yang nyata antara nilai kemapuan berpikir kreatif mahasiswa sebelum dan sesudah menggunakan PjBL berbasis video animasi rute pelayaran bangsa barat ke nusantara.